REACTION DIFFERENCES GROWTH INVESTOR AND VALUE INVESTOR TO EX-DIVIDEND DATE AND CHANGES IN DIVIDEND: EMPIRICAL STUDY ON LQ45 STOCK PERIOD 2008-2010 - Meri Dwi Anggraini; Agus Sutradjo; Meri Yani; Yulia Syafitri (Ikatan Dosen Menulis, 2024)
This research analyzes the differences in reactions growth investor And value investor to ex-dividend date and changes in dividend policy on LQ45 shares during the 2008-2010 period. Using approach event study, this study evaluates abnormal return And trading volume activity around ex-dividend date. The research results show that growth investor tend to do profit-taking before ex-dividend date, whereas value investor retain shares to obtain dividends. Dividend increases result abnormal return positive that is more appreciated by value investor, temporary growth investor tend to give neutral to negative responses. Conversely, a decrease in dividends results abnormal return negative which has more impact on value investor, temporary growth investor more tolerant of these changes. These findings support the theories of Dividend Signaling, Tax Preference, and Clientele Effect, which explain how investors with different preferences respond to dividend policy. This research provides insight for investors and companies in developing investment strategies and dividend policies that suit the characteristics of their investor base.